2005
DOI: 10.1111/j.1365-2141.2005.05736.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐related death in childhood acute lymphoblastic leukaemia in the Nordic countries: 1992–2001

Abstract: SummaryDespite continuously more successful treatment of childhood acute lymphoblastic leukaemia (ALL), 2-5% of children still die of other causes than relapse. The Nordic Society of Paediatric Haematology and Oncology-ALL92 protocol included 1652 patients £15 years of age with precursor Band T-cell ALL diagnosed between 1992 and 2001. Induction deaths and deaths in first complete remission (CR1) were included in the study. A total of 56 deaths (3%) were identified: 19 died during induction (1%) and 37 in CR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
4
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 26 publications
4
105
4
5
Order By: Relevance
“…7,10,11 The Nordic and Dutch groups, for example, in their definition of induction death, do not include children who die after achieving remission. 8,9 Thus, comparing our results with the results reported by these groups is problematic. Indeed, standard international definitions of TRM in acute leukemia are needed.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…7,10,11 The Nordic and Dutch groups, for example, in their definition of induction death, do not include children who die after achieving remission. 8,9 Thus, comparing our results with the results reported by these groups is problematic. Indeed, standard international definitions of TRM in acute leukemia are needed.…”
Section: Discussioncontrasting
confidence: 55%
“…In HICs, age, sex, high-risk status, higher initial WBC counts, T-cell lineage immunophenotype, and trisomy 21 have been associated with an increased risk of TRM. [7][8][9]11 In an Indian study, malnutrition, lymphadenopathy, and lower hemoglobin levels were associated with TRM. 13 In our previous study in El Salvador, we observed that socioeconomic variables predicted TRM, whereas biologic parameters did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the only two cases of intra-cranial haemorrhage during induction reported among over 2500 patients recruited to the current UK childhood ALL trial, UKALL 2003 (unpublished data) were associated with hyperleucocytosis in one and intra-cranial fungal infection in the other. This concords with the extremely low incidence of haemorrhagic deaths reported in older Nordic (Christensen et al, 2005), St Jude's (Ribeiro & Pui, 1986), UK (Wheeler et al, 1996) and German (Sutor et al, 1999) trials. In the German Berlin-Frankfürt-Münster (BFM) 90 trial (Sutor et al, 1999), there was no correlation between risk of serious haemorrhage and presence of coagulopathy or use of prophylactic plasma components and AT concentrates.…”
Section: The Risk Of Serious Haemorrhagementioning
confidence: 73%
“…Reports from several studies showed mortality due to infection as a form of side effects of chemotherapy and high-dose steroids (Conter et al 2009, Prucker et al 2009, Silverman et al 2000, Pui et al 2000, Christensen et al 2005. One cause of mortality due to infection in patients with LLA caused by glucocorticoids suppress adrenal inadequacy causing the body's defense against infection (Shulman et al 2007).…”
Section: Introductionmentioning
confidence: 99%